Improving polyglucan production in cyanobacteria and microalgae via cultivation design and metabolic engineering. Issue 6 (13th April 2015) - Aikawa, Shimpei; Ho, Shih‐Hsin; Nakanishi, Akihito; Chang, Jo‐Shu; Hasunuma, Tomohisa; Kondo, Akihiko
Abstract Photosynthetic microorganisms, such as cyanobacteria and microalgae, are currently being investigated as alternative biomass resources for bioethanol production, owing to their benefits, including high‐photosynthetic activity and whole‐year cultivation without utilization of arable land. Polyglucans comprise the major carbohydrate content of these organisms. Polyglucans can be utilized as a carbon source for microbial fermentation. Although polyglucan production has so far been promoted by nutrient limitation, it must be further enhanced to accommodate market demand. This review focuses on the recent progress in the production of α‐polyglucans such asglycogen and starch in cyanobacteria and green microalgae via cultivation design, including modifying the nutrient supply and replacing the growth medium. The control and manipulation of polyglucan metabolism necessitates the elucidation of the polyglucan production mechanism. We reviewed gene expression and metabolite accumulation profiles of cyanobacteria and green microalgae during nutrient limitation‐stimulated α‐polyglucan accumulation. We also focus on the enhancement in cyanobacterial glycogen production via the genetic engineering of glycolysis, CO2 concentration mechanism, and photosynthetic light‐harvesting protein based on the polyglucan accumulation mechanism. The combined strategies of cultivation design and genetic engineering should be considered for further enhancement of polyglucan productivity for bioethanol production.